2022
DOI: 10.1007/s12649-022-01854-2
|View full text |Cite
|
Sign up to set email alerts
|

Design of a Novel Hybrid Rice Straw/Husk Bio-Based Concrete Featuring Enhanced Mechanical and Hygrothermal Properties

Abstract: In order to reduce the consumption of energy and the emissions of greenhouse gases and CO 2 generated by the construction industry, bio-based concretes made of plant aggregates are increasingly used in the optimization of building envelopes thanks to their good hydrothermal performances, their renewable origin, and biodegradability. These insulation materials are considered as a promising alternative to synthetic systems made of mineral wool.This study investigates the use of a bio-based concretes performed wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 78 publications
0
1
0
Order By: Relevance
“…Among the three kinds of straw, the workability, strength, and insulation performance of concrete mixed with rape straw are better than those of wheat straw and corn straw. Moussi [41] investigated the effects of different proportions of rice straw and rice husk blended into concrete on thermal conductivity and mechanical properties. They found that increasing the content of rice straw reduced the thermal conductivity of concrete and that the thermal conductivity is inversely proportional to the porosity.…”
Section: Introductionmentioning
confidence: 99%
“…Among the three kinds of straw, the workability, strength, and insulation performance of concrete mixed with rape straw are better than those of wheat straw and corn straw. Moussi [41] investigated the effects of different proportions of rice straw and rice husk blended into concrete on thermal conductivity and mechanical properties. They found that increasing the content of rice straw reduced the thermal conductivity of concrete and that the thermal conductivity is inversely proportional to the porosity.…”
Section: Introductionmentioning
confidence: 99%